Development and Validation of a Prediction Model for the Cure of Peritoneal Dialysis-Associated Peritonitis: A Multicenter Observational Study - Meng, Lingfei; Yang, Liming; Zhu, Xueyan; Zhang, Xiaoxuan; Li, Xinyang; Cheng, Siyu; Guo, Shizheng; Zhuang, Xiaohua; Zou, Hongbin; Cui, Wenpeng (Frontiers in Medicine, 2022)
Aim Peritoneal dialysis (PD)-associated peritonitis (PDAP) is a severe complication of PD. It is an important issue about whether it can be cured. At present, there is no available prediction model for peritonitis cure. Therefore, the present work aimed to develop and validate a prediction model for peritonitis cure in PDAP patients. Methods PD patients who developed PDAP from four dialysis centers in Northeast China were followed up. According to the region of PD, data were divided into training and validation datasets. Initially, a nomogram for peritonitis cure was established based on the training dataset. Afterwards, the nomogram performance was assessed by discrimination (C-statistic), calibration and decision curves. Results Totally 1011 episodes of peritonitis were included in the final analysis containing 765 in the training dataset and 246 in the validation dataset. During the follow-up period, peritonitis cure was reported in 615 cases from training dataset and 198 from validation dataset. Predictors incorporated in the final nomogram included PD duration, serum albumin, antibiotics prior to admission, white cell count in peritoneal dialysate on day 5(/μL) ≥100/μL and type of causative organisms. The C-statistic values were 0.756 (95% CI: 0.713–0.799) in the training dataset and 0.756 (95% CI: 0.681–0.831) in the validation dataset. The nomogram exhibited favorable performance in terms of calibration in both the training and validation datasets. Conclusion This study develops a practical and convenient nomogram for the prediction of peritonitis cure in PDAP patients, which assists in the clinical decision-making.